2021
DOI: 10.3389/fpubh.2021.795869
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution of Public Health Expenditure Financed by the Romanian Social Health Insurance Scheme From 1999 to 2019

Abstract: The Romanian health system is mainly public financed (80.45%) through the following sources: Social Health Insurance (65%), State and Local Authorities Budget (15.45%), while the private sources (voluntary health insurance and out of pocket) adds an additional 19.55% to the public funds. The shares of the types of expenditure reflect the importance of each sector in the overall health system, and trends in expenditure show the impact of financing on the health sector's structural changes. We analyzed the 20-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
(6 reference statements)
2
13
0
Order By: Relevance
“…H1: The budgetary revenues from social assistance, under pandemic conditions, may be affected until the trend function changes in inverse proportion to budgetary revenues in the healthcare sector. This hypothesis is supported by a number of research studies ( 4 , 15 , 17 , 24 – 34 ) and is in line with Research Objective 1.…”
Section: Methodssupporting
confidence: 81%
See 3 more Smart Citations
“…H1: The budgetary revenues from social assistance, under pandemic conditions, may be affected until the trend function changes in inverse proportion to budgetary revenues in the healthcare sector. This hypothesis is supported by a number of research studies ( 4 , 15 , 17 , 24 – 34 ) and is in line with Research Objective 1.…”
Section: Methodssupporting
confidence: 81%
“…Some authors ( 4 ) highlight the fact that the medical system in Romania is strongly supported from public sources, the private contribution being around 20%. The authors make a forecast of the Social Health Insurance budget, which turns out to be on a strong upward trend.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Romania exploring health expenditure during 2009–2019 revealed an almost 5–15-fold increase in 5 years (after 2015), except for dentistry and multifunctional medical centers expenditures, where the increase was about 1–2-fold [ 35 ]. High-income countries with a higher value of GDP per capita spend more on healthcare in absolute terms [ 36 ], thus covering expensive technology and treatment due to an ageing population [ 37 ].…”
Section: Discussionmentioning
confidence: 99%